PENCEGAHAN DIABETES MELITUS DENGAN SOSIALISASI PENGGUNAAN INSULIN KEPADA MASYARAKAT DI KELURAHAN SUKORAME KOTA KEDIRI - Tridoso Sapto Agus Priyono; Arifani Siswidiasari; Henni Wati (Universitas Kadiri, 2025)
The low level of public knowledge about healthy lifestyles is one of the causes of the increasing incidence of Diabetes Mellitus, which is characterized by a continuous increase in blood glucose levels that can be complicated. The role of pharmacists can provide real evidence in reducing the incidence and morbidity of patients. Community Service Activities are carried out in the Sukorame Village community, Kediri City with the aim of increasing knowledge and insight into healthy lifestyles to prevent diabetes mellitus. Community Service Activities will carry out several community empowerment activities, namely: (1) Providing an introduction to diabetes mellitus and healthy lifestyles to prevent diabetes mellitus, (2). Conducting socialization on how to use insulin properly and correctly, (3). Providing assistance to the Sukorame Village community, Kediri City related to the proper use of insulin. The results of this activity were measured by pretest and posttest where knowledge about Diabetes Mellitus increased significantly and they were able to use insulin independently.